Effect of Spiritual Emotional Freedom Technique (SEFT) to Anxiety Patient Chronic Obstructive Pulmonary Disease (COPD) - Alwan Revai; Muhammad Amin; Makhfudli Makhfudli; Yuana Dwi Agustin (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: COPD can affect social and psychological aspects as well as physical health. Anxiety, loss of control in self-reliance, changes in self-concept and respiratory barriers result in serious psychological changes, including fear of death and depression. There is a significant relationship between depression and anxiety with sleep quality of chronic disease patients, the higher the degree of depression the worse the quality of sleep. Spiritual Emotional Freedom Technique (SEFT) is a therapy that uses spiritual elements to reduce psychological and physical problems caused by emotional or psychosomatic. Method: This study use Quasy Experiment "with Pre-Post test group control design approach. The population of this study was the patient of COPD in dr. H. Koesnadi Hospital and Bhayangkara Hospital at Bondowoso. Sampling was done by simple random sampling technique according to inclusion criteria with total 68 patients. SEFT intervention performed 8 times for 1 month. Instrument for anxiety using HARS. Data analysis using Mann Whitney Test. Result: There was a significant difference in the level of anxiety (p 0,000) between before and after SEFT therapy. Conclusion: SEFT can reduce anxiety levels of COPD patients, if done regularly and sustainably. The intervention focuses on reducing emotional or psychosomatic psychological problems.